QTL mapping and candidate gene identification for fodder quality traits in Pearl millet - Harmanpreet Singh Daduwal; Ruchika Bhardwaj; Jaspal Singh Lamba; Yogesh Vikal; Rakesh K. Srivastava (BMC Plant Biology)
Abstract Background Pearl millet is an excellent forage crop with significant potential for forage production. Its fodder is rich in protein, calcium, phosphorus and other essential minerals while being low in undesirable components such as hydrocyanic acid and oxalic acid. Globally, the shortage of high-quality fodder poses challenges for maintaining animal health and productivity, ultimately impacting dairy farmers. Therefore, improving pearl millet for fodder traits should be a priority to meet the global demand for nutritious livestock feed. Results Significant variability was observed for all forage quality related traits at both locations. A linkage map was constructed using 755 single-nucleotide polymorphisms (SNPs) markers, spanning a total length of 3080.44 cM. A total 8, 6 and 10 QTLs were identified for Ludhiana, Abohar and across the locations, respectively, for fodder quality. A common genomic interval with flanking markers S6_234379851- S6_64109715 was associated with IVOMD, CP and ME at all locations, with 10–34% phenotypic variance. Further, expression analysis identified BHLH 148, Resistance to phytophthora, Laccase 15, cytochrome P450, PLIM2c, GRF11, NEDD AXR1, NAC 92 and TF 089 as differentially expressed candidate genes in the leaf tissues of parental lines. A phylogenetic tree constructed using these genes revealed two clades identified with six paralogous events. Additionally, a phylogenetic tree of eight cereal species showed that the majority of shared similarity with the Pgl genes, suggestinga recent speciation event among them. Common genes, including cytochrome P450, PLIM2c, NEDD AXR1 and NAC domains were identified between QTL regions and expression analysis. Conclusion The differentially expressed genes incorporating the regulatory elements governing the lignin pathway have direct or indirect effects on fodder digestibility and quality. Exploiting these factors can contribute to the direct improvement of fodder quality. The identified QTLs and candidate genes from this study could facilitate the development of gene based markers for fodder improvement.